Managing knowledge integration in a national health-care crisis lessons learned from combating SARS in Singapore. - Devadoss, P.R (IEEE Transactions on information technology in biomedicine)
The outbreak of Severe Acute Respiratory Syndrome is the first severe and readily transmissible disease to emerge in the 21st century. Often one new infection meant tracing of several people to monitor their health conditions as well. In Singapore, several agencies coordinated their efforts to quickly bring the outbreak under control. The current breed of health-care information systems (HCIS) was not sufficient to handle new information-sharing needs during the crisis. In this paper, we take a look at the measures taken during the crisis in Singapore through a knowledge integration perspective. This perspective reveals interesting implications for HCIS.